2019
DOI: 10.1136/bmjopen-2019-032062
|View full text |Cite
|
Sign up to set email alerts
|

Inequality of trauma care under a single-payer universal coverage system in Taiwan: a nationwide cohort study from the National Health Insurance Research Database

Abstract: ​ObjectivesTo assess the impact of lower socioeconomic status on the outcome of major torso trauma patients under the single-payer system by the National Health Insurance (NHI) in Taiwan.​DesignA nationwide, retrospective cohort study.​SettingAn observational study from the NHI Research Database (NHIRD), involving all the insurees in the NHI.​ParticipantsPatients with major torso trauma (injury severity score ≥16) from 2003 to 2013 in Taiwan were included. International Classification of Disease, Ninth Revisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Trauma surgeons frequently encounter chest trauma. Approximately 40% of patients with an injury severity score (ISS) greater than 16 had concomitant thoracic injuries in Taiwan [ 1 ], and these injuries are accountable for up to 25% of trauma deaths [ 2 ]. Rib fractures are the most common thoracic injury in patients who sustained blunt trauma, and associated injuries with potential life-threatening outcomes often occur in these patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trauma surgeons frequently encounter chest trauma. Approximately 40% of patients with an injury severity score (ISS) greater than 16 had concomitant thoracic injuries in Taiwan [ 1 ], and these injuries are accountable for up to 25% of trauma deaths [ 2 ]. Rib fractures are the most common thoracic injury in patients who sustained blunt trauma, and associated injuries with potential life-threatening outcomes often occur in these patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there were a few patients with an AIS equal or larger than 3 in extremities, which explains the presence of AIS and ISS in this study group. Previous studies have shown that the survival of such patients was less influenced by injuries to the extremities, but mostly by injuries to the torso region [1, 2]. The imprecise terminology does not bias the conclusion of this study.…”
mentioning
confidence: 77%
“…The common implementation mechanisms that support UHC include health insurance, a social health justice policy, digital financing systems, and partnerships (Table 1). ) is a form of free government-owned healthcare provided to everyone, while citizen should pay for income tax revenue (72,(75)(76)(77)(78)(79)(80)(81). There are also mixed health plans, such as applying Medicare as a public health insurance and purchasing private hospital coverage or paying a tax surcharge as subsidized private care (82,83).…”
Section: How Does Universal Health Coverage Work?mentioning
confidence: 99%